3D Lagrangian particle tracking of a subsonic jet using multi-pulse Shake-The-Box - Manovski, Peter; Novara, Matteo; Karthik, Nagendra; Mohan, Depuru; Geisler, Reinhard; Schanz, Daniel; Agocs, Janos; Godbersen, Philipp; Schröder, Andreas (Elsevier, 2021)
Three-dimensional (3D) Lagrangian Particle Tracking (LPT) was performed on a subsonic jet flow at Mach 0.506 and 0.845 generated by a round nozzle with diameter-based Reynolds numbers of 1.7×105 and 3.1×105, respectively. The Multi-Pulse Shake-The-Box (MP-STB) technique was employed to reconstruct particle tracks along the four-pulse sequences, which were obtained by using orthogonally polarised light to separate the pulses on camera images. The MP-STB method applied here has a number of differences compared to previous publications, in particular, a new adaptive search radii approach and an iterative strategy and particle track validation criteria that have been customised for high subsonic/transonic flows. A description of this methodology is given followed by presentation of the instantaneous 3D flow velocity and material acceleration particle tracks. By ensemble-averaging the scattered instantaneous measurements extracted from individual particle tracks into small volumetric bins, highly resolved statistical quantities were obtained. The performance of MP-STB was assessed by comparing velocity profiles with published particle image velocimetry (PIV) data-sets. MP-STB was better able to resolve the steep velocity gradients, in particular the thin jet shear layer near the nozzle exit. At this location the MP-STB results also yielded higher turbulence intensities compared with the reported studies for similar flow conditions. The MP-STB acceleration flow statistics were compared for the two Mach numbers, and for the Mach 0.506 case, higher levels of normalised acceleration and fluctuations were found. The position accuracy of the 3D imaging system was quantified and it was found that the use of two different states of polarisation had a direct impact on the accuracy and the amount successfully tracked particles. Further assessment of the particle imaging quality of each camera revealed a significant disparity between cameras. This was attributed to the particle light scattering intensity variations, which were highly dependent on the particle size, camera angles and different states of polarised light. Despite these challenges, an average of40,000 individual particle tracks could be reconstructed from a typical particle image density of 0.02 particles per px (and an active sensor area of 1800×2200 px2). Furthermore, the accuracy of the measurement was shown to be relatively high, with respect to PIV.
Keywords: Shear Layer; Shake-The-Box; Particle Image Velocimetry; Lagrangian Particle Tracking; Jet